2017
DOI: 10.1002/ange.201709441
|View full text |Cite
|
Sign up to set email alerts
|

A Manganese Pre‐Catalyst: Mild Reduction of Amides, Ketones, Aldehydes, and Esters

Abstract: Anew (N-phosphinoamidinate)manganesecomplex is shown to be au seful pre-catalyst for the hydrosilative reduction of carbonyl compounds,a nd in most cases at room temperature.The Mn-catalyzed reduction of tertiary amides to tertiary amines,with auseful scope,isdemonstrated for the first time by use of this catalyst, and is competitive with the most effective transition-metal catalysts knownfor such transformations.K etones,a ldehydes,a nd esters were also successfully reduced under mild conditions by using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Control experiments confirmed that no reaction took place under the screening conditions in the absence of a manganese complex. Even though there are reports of manganese(II) pincer complexes showing good activity in a range of other hydrosilylation reactions, 45 47 manganese(II) and manganese(III) salts like MnCl 2 , MnBr 2 , Mn(OAc) 2 ·(H 2 O) 4 , and Mn(OAc) 3 ·(H 2 O) 2 did not afford any product. The reaction could be carried out with good to excellent yields in a broad range of solvents, including even neat conditions ( Table 1 ).…”
Section: Resultsmentioning
confidence: 98%
“…Control experiments confirmed that no reaction took place under the screening conditions in the absence of a manganese complex. Even though there are reports of manganese(II) pincer complexes showing good activity in a range of other hydrosilylation reactions, 45 47 manganese(II) and manganese(III) salts like MnCl 2 , MnBr 2 , Mn(OAc) 2 ·(H 2 O) 4 , and Mn(OAc) 3 ·(H 2 O) 2 did not afford any product. The reaction could be carried out with good to excellent yields in a broad range of solvents, including even neat conditions ( Table 1 ).…”
Section: Resultsmentioning
confidence: 98%